SUDDEN CARDIAC DEATH: VULNERABILITY OF ATHEROSCLEROTIC PLAQUE IN CORONARY ARTERIES: Atherosclerotic Plaque in Coronary Arteries - Bukhsh, Sumaira; Nasreen, Samia; Tariq, Hassan; Ali, Syed Salman; Umer, Muhammad; Zafar, Nadeem; Din, Hafeez Ud (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the vulnerability of atherosclerotic plaque in coronary arteries of individuals dying of ischemic heart disease.Study Design: Cross sectional study.Place and Duration of Study: Histopathology department, Combined Military Hospital Lahore, from Nov 2016 to Nov 2017.Methodology: A total of 43 cases were taken in the study. The Autopsy specimens from the bodies of people dying suddenly of ischemic heart disease were taken into the study. Tissues showing autolytic changes and patients dying with coronary artery disease after corrective procedure like stenting and bypass were excluded.Results: Out of 43 cases, 35 (81.4%) cases were positive for cluster of differentiation 68 (CD 68), 34 (79%) cases were positive for cluster of differentiation 105 (CD 105) & 36 (83.6) cases were positive for nuclear factor kappa-light-chain-enhancer of activated B cells (NF-Kb).Conclusion: People who had died of ischemic heart disease have more vulnerable plaque in their coronary arteries as compared to the people who had died of non-ischemic cause. Early recognition of the un-ruptured plaque is important for the treatment strategies.